Perlindungan Hukum Terhadap Perempuan dalam Perkawinan yang Dilakukan Secara Paksaan Berdalih Tradisi Perspektif Kesetaraan Gender - Angliati Deltia Kamuri Mawo Ate; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2025)
Marriage is synonymous with love and happiness between men and women and the Indonesian state guarantees by providing a legal umbrella that every Indonesian citizen has the right to build a strong family without coercion in building a household. The practice of forced marriage that occurs on Sumba Island often reaps controversy because the value of this tradition leads to kidnapping and violation of women's rights. For this tradition a woman is forced to marry a man she does not know and does not even love for culturally legalized reasons. Problem formulation: How is the legal protection of women in forced marriage from the perspective of gender equality and what are the legal consequences of forced marriage under the pretext of tradition with regard to women's rights in gender equality. This research uses the normative type, analyzing various literatures, relevant law books such as laws and regulations, norms and also legal principles relating to the practice of forced marriage.